Planar Formation Control of a School of Robotic Fish: Theory and Experiments - Paley, Derek A.; Thompson, Anthony A.; Wolek, Artur; Ghanem, Paul (Frontiers in Control Engineering, 2021)
This paper presents a nonlinear control design for the stabilization of parallel and circular motion in a school of robotic fish actuated with internal reaction wheels. The closed-loop swimming dynamics of the fish robots are represented by the canonical Chaplygin sleigh, and they exchange relative state information according to a connected, undirected communication graph to form a system of coupled, nonlinear, second-order oscillators. Prior work on collective motion of constant-speed, self-propelled particles serves as the foundation of our approach. However, unlike a self-propelled particle, the fish robots follow limit-cycle dynamics to sustain periodic flapping for forward motion with time varying speed. Parallel and circular motions are achieved in an average sense without feedback linearization of the agents' dynamics. Implementation of the proposed parallel formation control law on an actual school of robotic fish is described, including system identification experiments to identify motor dynamics and the design of a motor torque tracking controller to follow the nonlinear formation control reference torque commands. Experimental results are presented that demonstrate a school of four robotic fish achieving parallel formations starting from random initial conditions.